Antineoplastic drugs determination by HPLC‐HRMSn to monitor occupational exposure. Issue 7 (4th June 2015) - Dal Bello, Federica; Santoro, Valentina; Scarpino, Valentina; Martano, Chiara; Aigotti, Riccardo; Chiappa, Alberta; Davoli, Enrico; Medana, Claudio
Abstract : The purpose of this study was to develop a simple, direct, multiresidue highly specific procedure to evaluate the possible surface contamination of selected antineoplastic drugs in several hospital environment sites by using wipe test sampling. 5‐fluorouracil (5‐FU), carboplatin (C‐Pt), cyclophosphamide (CYC), cytarabine (CYT), doxorubicin (DOX), gemcitabine (GEM), ifosfamide (IFO), methotrexate (MET), and mitomycin C (MIT) belong to very different chemical classes but show good ionization properties under electrospray ionization (ESI) conditions (negative ion mode for 5‐FU and positive ion mode in all other cases). HPLC (high performance liquid chromatography) coupled with HRMS (high resolution mass spectrometry) appears to be the best technique for direct analysis of these analytes, because neither derivatization nor complex extraction procedure for polar compounds in samples is requested prior the analysis. Sample preparation was limited to washing wipes with appropriate solvents. Chromatographic separation was achieved on C18 reversed phase columns. The HPLC‐HRMS/MS method was validated in order to obtain robustness, sensitivity and selectivity. LLOQ (lower limit of quantitation) values provided a sensitivity good enough to evidence the presence of the drugs in a very low concentration range (<1 pg/cm 2 ). The method was applied for a study of real wipe tests coming from many areas from a hospital showing some positive samples. The low quantitation limits and the high specificity due to the high resolution approach of the developed method allowed an accurate description of the working environment that can be used to define procedural rules to limit working place contamination to a minimum. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Monitoring toxic drugs in hospitals is mandatory to improve occupational safety. A multiresidual, simple and fast method to follow occupational pollution is showed. HRMS is a novel approach to detecting drugs residues and their decomposition/metabolism products with high selectivity/sensitivity.